Comparison of Relative Value Units and 30-Day Outcomes Between Primary and Revision Pediatric Spinal Deformity Surgery. Issue 1 (7th February 2023) - Song, Junho; Katz, Austen D.; Dalal, Sidhant; Silber, Jeff; Essig, David; Qureshi, Sheeraz; Virk, Sohrab
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to compare the relative value units (RVUs) and 30-day outcomes between primary and revision pediatric spinal deformity (PSD) surgery. Summary of Background Data: PSD surgery is frequently complicated by the need for reoperation. However, there is limited literature on physician reimbursement rates and short-term outcomes following primary versus revision spinal deformity surgery in the pediatric population. Materials and Methods: This study utilizes data obtained from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) Pediatric database. Patients between 10 and 18 years of age who underwent posterior spinal deformity surgery between 2012 and 2018 were included. Univariate and multivariate regression were used to assess the independent impact of revision surgery on RVUs and postoperative outcomes, including 30-day readmission, reoperation, morbidity, and complications. Results: The study cohort included a total of 15, 055 patients, with 358 patients who underwent revision surgery. Patients in the revision group were more likely to be younger and male sex. Revision surgery more commonly required osteotomy (13.7% vs. 8.3%, P =0.002). Univariate analysis revealed higher total RVUs (71.09 vs. 60.51, P <0.001), RVUs per minute (0.27 vs. 0.23, P <0.001), readmission rate (6.7% vs. 4.0%, P =0.012), and reoperation rate (7.5% vs. 3.3%, P <0.001) for the revision surgery group. Morbidity rates were found to be statistically similar. In addition, deep surgical site infection, pulmonary embolism, and urinary tract infection were more common in the revision group. After controlling for baseline differences in multivariate regression, the differences in total RVUs, RVUs per minute, reoperation rate, and rate of pulmonary embolism between primary and revision surgery remained statistically significant. Conclusions: Revision PSD surgery was found to be assigned appropriately higher mean total RVUs and RVUs per minute corresponding to the higher operative complexity compared with primary surgery. Revision surgery was also associated with poorer 30-day outcomes, including higher frequencies of reoperation and pulmonary embolism. Level of Evidence: Level III.